Relationships between anthropometric measures and athletic performance, with special reference to repeated-sprint ability, in the Qatar national soccer team - Brocherie, F.; Girard, O.; Forchino, F.; Al Haddad, H.; dos Santos, G. A.; Millet, G. P. (Journal of Sports Sciences, 2014)
The aim of this study was to determine potential relationships between anthropometric parameters and athletic performance with special consideration to repeated-sprint ability (RSA). Sixteen players of the senior male Qatar national soccer team performed a series of anthropometric and physical tests including countermovement jumps without (CMJ) and with free arms (CMJwA), straight-line 20 m sprint, RSA (6 × 35 m with 10 s recovery) and incremental field test. Significant (P < 0.05) relationships occurred between muscle-to-bone ratio and both CMJs height (r ranging from 0.56 to 0.69) as well as with all RSA-related variables (r < -0.53 for sprinting times and r = 0.54 for maximal sprinting speed) with the exception of the sprint decrement score (Sdec). The sum of six skinfolds and adipose mass index were largely correlated with Sdec (r = 0.68, P < 0.01 and r = 0.55, P < 0.05, respectively) but not with total time (TT, r = 0.44 and 0.33, P > 0.05, respectively) or any standard athletic tests. Multiple regression analyses indicated that muscular cross-sectional area for mid-thigh, adipose index, straight-line 20 m time, maximal sprinting speed and CMJwA are the strongest predictors of Sdec (r2 = 0.89) and TT (r2 = 0.95) during our RSA test. In the Qatar national soccer team, players` power-related qualities and RSA are associated with a high muscular profile and a low adiposity. This supports the relevance of explosive power for the soccer players and the larger importance of neuromuscular qualities determining the RSA.